THE IMPORTANCE OF THE MEMORY PROCESS IN HUMAN LIFE (Archive of Conferences, 2021)
Memory is very important in human life. Memory not only reflects the things and events of the present, but also the things and events of the past, the feelings and thoughts that we experience. When we didn't have memory, we only reflected what was being perceived and what was happening, and what was being perceived always seemed new and unfamiliar to us. Memory develops skills and abilities, enriches knowledge and expands the level. Memory is of great importance for the functioning and development of other mental processes